Allelopathic Potential of Bidens pilosa L. Extracts on seed Germination and Seedling Development of Lettuce and Chicory - Bandeira, Arlete da Silva; Boaventura, Caroline; Gugé, Romana Mascarenhas Andrade; Amaral, Maria Caroline Aguiar; Castro Filho, Manoel Nelson de; Cardoso, Adriana Dias; Fernandes, Nilglaudson de Sousa (Revista de Ciências Agroveterinárias, 2024)
Vegetable cultivation has significant socioeconomic importance, and Bidens pilosa L. is a weed with allelopathic effects that can reduce the germination of vegetable seeds and impair their initial development. This study aimed to determine the allelopathic potential of B. pilosa on the germination and initial development of lettuce and chicory seeds. Two separate trials were conducted, one with lettuce seeds and the other with chicory seeds. Germination and vigor tests were carried out in petri dishes and arranged in a completely randomized design, with four concentrations of aqueous extract of Bidens p. (0, 20, 60, and 100%) and five replications, totaling 20 experimental plots. The evaluated characteristics were: number of days to start germination, number of days to finish germination, germination percentage, germination speed index, average germination time, root length, and hypocotyl length. The number of days to start germination and the average germination time of lettuce and chicory seeds were greater as the concentration of aqueous extracts of B. pilosa increased. With increasing extract concentrations, the germination percentage, germination speed index, root length, and hypocotyl length of lettuce and chicory seedlings were reduced. The aqueous extract of B. pilosa leaves exhibited inhibitory allelopathic activity on the physiology of germination and the development of lettuce and chicory seedlings.